Compassion Fatigue, Compassion Satisfaction and Related Factors in Pediatric Wards: A Narrative Review Study - Nargess Pakdaman MA; Azam Naghavi PhD; Fatemeh Samiee PhD; Faramarz Kalhor (Global Pediatric Health)
Working with chronically ill children can overwhelm for professionals. It is necessary to study the factors related to compassion fatigue and satisfaction in order to effectively deal with it. Using a narrative review and inclusion criteria, we searched online databases for related studies from 2000 to 2023. Twelve articles were included in the final review. Understanding compassion fatigue/satisfaction will help to solve personal and professional problems and increase productivity, leading to positive outcomes for the patient, family, and the organization. This study identifies several factors that contribute to compassion fatigue (CF) in pediatric healthcare providers. These factors include workload, patient connections, lack of support, exposure to trauma, personal trauma, job dissatisfaction, and neglecting self-care. It is crucial to address these factors through targeted interventions and organizational support. Implementing evidence-based interventions shows promise in reducing the impact of CF, fostering a resilient healthcare workforce, and improving patient care.